2006
DOI: 10.1007/s12022-006-0008-y
|View full text |Cite
|
Sign up to set email alerts
|

Cytokeratin CK20 is a sensitive marker for Crooke's cells and the early cytoskeletal changes associated with hypercortisolism within pituitary corticotrophs

Abstract: Crooke's cells are nonneoplastic corticotroph cells found in the adenohypophysis of patients who have an endogenous or exogenous excess of glucocorticoids. Classic Crooke's cells have a prominent hyaline cytoplasmic ring that displaces the basophilic granules of the normal cell. This characteristic appearance is produced by a perinuclear accumulation of cytokeratin filaments. Immunohistochemistry for cytokeratins is a sensitive way to identify Crooke's cells, but a keratin antibody specific for Crooke's hyalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…9 This pattern of reactivity has also been described in neoplastic cells of corticotroph tumors and in non-neoplastic cells of patients with endogenous and exogenous hypercortisolism. 11 In our CK20-positive tumors, Crooke's hyaline change was not prominently identified, reflecting the fact that most tumors, including corticotrophs, were macroadenomas.…”
Section: Expression Of Ck20 In Pituitary Adenomamentioning
confidence: 71%
See 3 more Smart Citations
“…9 This pattern of reactivity has also been described in neoplastic cells of corticotroph tumors and in non-neoplastic cells of patients with endogenous and exogenous hypercortisolism. 11 In our CK20-positive tumors, Crooke's hyaline change was not prominently identified, reflecting the fact that most tumors, including corticotrophs, were macroadenomas.…”
Section: Expression Of Ck20 In Pituitary Adenomamentioning
confidence: 71%
“…Thus, we found this more frequently than in prior studies reporting no CK20‐positive tumors but less frequently than in studies where CK20 reactivity was a frequent finding . This pattern of reactivity has also been described in neoplastic cells of corticotroph tumors and in non‐neoplastic cells of patients with endogenous and exogenous hypercortisolism . In our CK20‐positive tumors, Crooke's hyaline change was not prominently identified, reflecting the fact that most tumors, including corticotrophs, were macroadenomas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The distinction between densely granulated and sparsely granulated growth hormone producing tumors is of clinical importance, as densely granulated somatotroph adenomas are more likely to respond to somatostatin analog therapy compared with sparsely granulated adenomas [55,56]. In normal and hyperplastic anterior pituitary tissue, corticotroph secreting cells (Crooke's cells) are positive for K20 [57]. Coons et al reported that 13 of 15 cases of corticotroph adenomas constantly expressed K20 with a diffuse cytoplasmic pattern, making K20 a very useful marker for this specific type of adenoma [58].…”
Section: Pituitary Glandmentioning
confidence: 99%